Technology blueprint : (ultra-durable sports leggings) / Amirah lsmail...[et al.] - lsmail, Amirah; Mahadzir, Intan Mutiara; Ishak, Nur Amira; Mohd Razif, Muhammad Ilyas (2019)
The main focus of the business is to create unique tights for sports athletes. These tights are a revolutionary concept that emerges from athletes' common fears whose tights ar~ten ripp~ and don't last. Our trademark of the brand is to "play without hesitating". For the target market and the projection, our company has a community target that requires our products like a sportsman. This is because they always want the best products and help improve the productivity of their daily lives. The target for this product for sportsmen and suitable for all which means everybody can get the opportunity to try this innovation product. This product will be modernized by a new design in the future. FoIYCompetitive advantage, it can have a positive impact on this product, as each se~Zl be carefully studied to compete with well-known brands in the current marjse~Besides, our company will constantly improve on all aspects to ensure that th~tfuct being produced satisfies buyers and provides positive feedback for a better future. The management team consists of general manager, marketing manager, administration manager, operational manager, and financial manager. Each of the managers has the responsibility to ensure that everything is carefully researched to ,avoid any problems that may arise with the production of this product.